Activation of C-Type Lectin Receptor and (RIG)-I-Like Receptors Contributes to Proinflammatory Response in Middle East Respiratory Syndrome Coronavirus-Infected Macrophages. (28th September 2019) - Zhao, Xiaoyu; Chu, Hin; Wong, Bosco Ho-Yin; Chiu, Man Chun; Wang, Dong; Li, Cun; Liu, Xiaojuan; Yang, Dong; Poon, Vincent Kwok-Man; Cai, Jianpiao; Chan, Jasper Fuk-Woo; To, Kelvin Kai-Wang; et al.
Abstract: Background: Human infection with Middle East respiratory syndrome coronavirus (MERS-CoV) poses an ongoing threat to public health worldwide. The studies of MERS patients with severe disease and experimentally infected animals showed that robust viral replication and intensive proinflammatory response in lung tissues contribute to high pathogenicity of MERS-CoV. We sought to identify pattern recognition receptor (PRR) signaling pathway(s) that mediates the inflammatory cascade in human macrophages upon MERS-CoV infection. Methods: The potential signaling pathways were manipulated individually by pharmacological inhibition, small interfering ribonucleic acid (siRNA) depletion, and antibody blocking. The MERS-CoV-induced proinflammatory response was evaluated by measuring the expression levels of key cytokines and/or chemokines. Reverse transcription-quantitative polymerase chain reaction assay, flow cytometry analysis, and Western blotting were applied to evaluate the activation of related PRRs and engagement of adaptors. Results: MERS-CoV replication significantly upregulated C-type lectin receptor (CLR) macrophage-inducible Ca 2+ -dependent lectin receptor (Mincle). The role of Mincle for MERS-CoV-triggered cytokine/chemokine induction was established based on the results of antibody blockage, siRNA depletion of Mincle and its adaptor spleen tyrosine kinase (Syk), and Syk pharmacological inhibition. The cytokine and/or chemokine induction was significantly attenuated by siRNA depletion of retinoic acid-inducible-I-like receptors (RLR) or adaptor, indicating that RLR signaling also contributed to MERS-CoV-induced proinflammatory response. Conclusions: The CLR and RLR pathways are activated and contribute to the proinflammatory response in MERS-CoV-infected macrophages.